Preoperative Falls and Their Association with Functional Dependence and Quality of Life. (August 2016) - Kronzer, Vanessa L.; Tang, Rose D.; Schelble, Allison P.; Ben Abdallah, Arbi; Wildes, Troy S.; McKinnon, Sherry L.; Sadiq, Furqaan; Lin, Nan; Helsten, Daniel L.; Sharma, Anshuman; Stark, Susan L.; Avidan, Michael S.
Abstract : Background: No study has rigorously explored the characteristics of surgical patients with recent preoperative falls. Our objective was to describe the essential features of preoperative falls and determine whether they are associated with preoperative functional dependence and poor quality of life. Methods: This was an observational study involving 15, 060 surveys from adult patients undergoing elective surgery. The surveys were collected between January 2014 and August 2015, with a response rate of 92%. Results: In the 6 months before surgery, 26% (99% CI, 25 to 27%) of patients fell at least once, and 12% (99% CI, 11 to 13%) fell at least twice. The proportion of patients who fell was highest among patients presenting for neurosurgery (41%; 99% CI, 36 to 45%). At least one fall-related injury occurred in 58% (99% CI, 56 to 60%) of those who fell. Falls were common in all age groups, but surprisingly, they did not increase monotonically with age. Middle-aged patients (45 to 64 yr) had the highest proportion of fallers (28%), recurrent fallers (13%), and severe fall-related injuries (27%) compared to younger (18 to 44 yr) and older (65+ yr) patients ( P < 0.001 for each). A fall within 6 months was independently associated with preoperative functional dependence (odds ratio, 1.94; 99% CI, 1.68 to 2.24) and poor physical quality of life (odds ratio, 2.18; 99% CI, 1.88 to 2.52). Conclusions: Preoperative falls might be common and are possibly often injurious in the presurgical population, across all ages. A history of falls could enhance the assessment of preoperative functional dependence and quality of life. Abstract : Observational study of more than 15, 000 adults undergoing elective surgery found that 26% fell in the 6 months preceding surgery, and more than half of these falls caused injuries. Even after adjustment for known confounding factors, preoperative falls were associated with a two-fold increase in both preoperative functional dependence and poor physical quality of life.